Optimum Growth Parameters for Both Indoor and Outdoor Propagation of Microalgae,Chlorella Vulgaris and Isochrysis Galbana - Muhamad Shaleh, Sitti Raehanah (2004)
Chlorella vulgaris and Isochrysis galbana were grown under different growth conditions both in indoor and outdoor cultures. Best culture conditions such as light intensities, photoperiods, salinities and nutrient concentrations were determined as well as the biochemical compositions. Indoor cultures of C. vulgaris and I. galbana, when continuously illuminated, grew optimally at 100 μmolm-2s-1 and 40 μmolm-2s-1, respectively. However, under 12 hour light, C. vulgaris grew optimally at 200 μmolm-2s-1. The chlorophylla concentrations in both algae were lower at higher light intensity and higher at lower light intensity. Total protein and total lipid contents of both species were also significantly higher (p<0.05) at lower light intensity. I. galbana contained more lipid than C. vulgaris in those conditions. In contrast to protein and lipid, carbohydrate content increased with increasing light intensity. Similar to C. vulgaris, the lowest carbohydrate content of I. galbana was obtained at l0 μmolm-2s-1 conditions for both photoperiods. Although the protein contents of C. vulgaris varied under different light intensity and photoperiod, the relative proportions of constituent amino acids were found to be almost similar. Total essential amino acids under continuous illumination was significantly higher (p<0.05) at the lowest and the highest intensities while in I. galbana, it was significantly higher (p<0.05) only at the lowest intensity. It was surprising that C. vulgaris contained high proportions of ω-3 highly unsaturated fatty acids at continuous illuminations although both eicosapentaenoic acid (20:5ω-3) and docosahexaenoic acid (22:6ω-3) were absent at 12 hours light. EPA in I. galbana, was absent at 12 hours light, while the DHA was present in relatively smaller quantities than in continuous light. In indoor conditions, at full media concentration, the best salinity for C. vulgaris was at 30 ppt and 25 ppt for I. galbana. C. vulgaris grown in full media concentration contained more chlorophylla relative to that in half media concentration. For I. galbana grown in full media concentration, chlorophylla increased as salinity increased. Protein contents decreased as salinity increase both at full and half strength media for C. vulgaris and I. galbana. The cellular lipid contents of both algae were significantly higher (p<0.05) in half media concentration. In full media concentration, total lipid contents in C. vulgaris decreased at higher salinity but in I. galbana no clear trend in lipid contents in relation to salinity observed. As salinity increased, higher carbohydrate contents were found in C. vulgaris in full media concentration, while in half media concentration an inverse trend was detected. I. galbana also revealed higher proportions of total carbohydrates in half media concentration compared to full media concentration. The amino acid profile of both algae exhibited minor differences at different salinity and media concentrations. Most of the essential amino acid in C. vulgaris and I. galbana were significantly higher (p<0.05) at lower salinity. In C. vulgaris, the EPA was absent while only trace amount of DHA were detected in cells grown under full media concentration. However in I. galbana the amount of EPA was very high at higher salinity and in contrary the, DHA was higher at lower salinity. The growth performances of C. vulgaris outdoor cultures were relatively better than I. galbana under all growth conditions studied. C. vulgaris grown both in unsheltered and sheltered areas demonstrated rapid increased in cell density after four days of culture with no lag phases observed. Unlike C. vulgaris, cultures of I. galbana grown under unshaded conditions demonstrated increase in cell numbers for 2 days but cells under sheltered place demonstrated no increased at all. The highest specific growth rate in C. vulgaris was in lower salinity at half media concentration while the maximum cell density was achieved by cells in full media concentration of the same salinity. For I. galbana cells density of half media concentration was higher then in full media concentration. The highest total protein content of C. vulgaris was obtained in culture under shaded conditions and generally total lipid and carbohydrate were found to be higher in unshaded conditions. However, it was unexplainable why less carbohydrate was found in older cells at both conditions. I. galbana was a fast growing algae and the protein as well as lipid contents were significantly higher (p<0.05) at sheltered condition while no significant changes to carbohydrate content was recorded. The carbohydrate content in C. vulgaris was higher in older cultures in full and half media concentration while at early culture age, the lipid content was higher. In the early culture age of I. galbana, protein content was insignificantly affected (p>0.05) by salinity and media concentration. However, total lipid and carbohydrate were found higher at 15 ppt compared to higher salinity in half media concentration. In the bioeconomic study the production cost of C. vulgaris was found to be directly influenced by labour cost. From the production forecast, it was discovered that the high production cost was due to underutilized labour force which can be reduced by having bigger scale production. In order to break-even for one cycle of 100 L cultures, the minimum culture volume should be 1,902 litres.